“The Boundless Realm Where All Form Lies”. Representing Imagination at the Crossway Between Literary and Neurocognitive Studies - Gambino, Renata; Pulvirenti, Grazia (Frontiers in Integrative Neuroscience, 2021)
In studies on poetics and aesthetics, the concept of representation is deeply bound to that of “mimesis”; this last was intended in two main ways: as “imitation” and as “world-construction”. In Aristotle’s Poetics, mimesis is theorized as the main form of “world-simulation”, giving rise to the complex universe of fiction. The concept of simulation plays a pivotal role in the neurocognitive theories on the embodied mind, within which embodied simulation is intended as a functional pre-linguistic activation of the human sensorimotor mechanism also in relation to the process of imagination giving rise to literary imagery and to the reader’s reception of the fictional world, since human beings share a common sensorimotor apparatus. Imagination is a central concept in the recent neurocognitive studies since it plays a core role in human life and in artistic production and reception. Imagination has been considered as a complex emergent cognitive faculty deeply intertwined with perception, memory and consciousness, shaping human life and transforming the limited horizon of our perceptual affective understanding, being and acting. In this paper we claim that scientific researches may take advantage from the literary representation of the imaginative faculties, which occurs in peculiar tests characterized by dynamic images and motion. In such meta-representation of the imagination, we assist to the phenomenological emergence of the endogenous dynamic processes involving a cluster of cognitive faculties activated by triggering the reader’s embodied simulation, in order to construct meaning through the creation of aesthetic forms. The aim of this study is to point out the dynamic emergent qualities of imagination as meta-represented in literature. In our opinion, these features are inherent and quintessential to the imagination as a cognitive and creative faculty. In this sense goes our claim to further studies in the field of a transdisciplinary venture inquiring the still uncharted aspects of the imagination as a circular phenomenon which cannot be understood in abstract terms as a mind minor property but needs to be investigated as a reproductive and productive representative power with regard to both its creative and receptive aspects.